2014
DOI: 10.1136/bjophthalmol-2013-304277
|View full text |Cite
|
Sign up to set email alerts
|

Corneal biomechanical properties of patients with acromegaly

Abstract: These findings indicate that acromegaly has target organ effects on the eye. Consequently, it can change corneal biomechanical properties such as corneal hysteresis and the CRF. Corneal biomechanical properties are known to affect the accuracy of IOP measurements. These findings should be taken into account when measuring IOP values in acromegaly patients, as IOP readings may be overestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
1
11
0
4
Order By: Relevance
“…The difference with our data may be attributed to the extreme range of CCT for . In a recent study using the Ocular Response Analyzer, Ozkok et al [28] reported that patients with acromegaly had significantly different Fig. 2 Scatter-plot of intraocular pressure vs. growth hormone serum levels for acromegalic patients Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The difference with our data may be attributed to the extreme range of CCT for . In a recent study using the Ocular Response Analyzer, Ozkok et al [28] reported that patients with acromegaly had significantly different Fig. 2 Scatter-plot of intraocular pressure vs. growth hormone serum levels for acromegalic patients Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ile Altınkaynak ve ark., KH ve KRF değerlerini akromegali hastalarında anlamlı olarak yüksek bulur iken; Şen ve ark., KH ve KRF değerlerini akromegali hasta grubunda daha yüksek ölçmüş, ancak aradaki farkı istatistiksel olarak anlamlı bulmamışlardır. [8][9][10] Bu farklı sonuçların iki çalışmaya dâhil edilen akromegali hasta gruplarındaki hormon düzeyleri kontrol altında olan ve olmayan hasta oranlarının farklı olmasından kaynaklanabileceği belirtilmiştir. Çalışmamızda ise KH, akromegali hastalarında sağlıklı kontrol grubuna göre istatistiksel olarak anlamlı bir farkla daha yüksek bulunur iken, KRF istatistiksel olarak anlamlı düzeyde düşük saptanmıştır.…”
Section: Bulgularunclassified
“…GİBg değerindeki bu yüksekliği korneanın biyomekanik özeliklerindeki değişikliklere bağlamışlardır. 6,9,10 Şen ve ark. ise GİBkk ve GİBg değerlerinde akromegali hasta grubu ile sağlıklı kontrol grubu arasında anlamlı fark saptamamışlardır.…”
Section: Bulgularunclassified
See 2 more Smart Citations